Turner's last sketchbook - Turner, Joseph Mallord William 1775-1851 (Yale Center for British Art, 2024)
"J. M. W. Turner (1775-1851) seldom left home without a sketchbook. Over the course of his lifetime, he filled more than three hundred, most of them small enough to carry in his pocket. This facsimile represents Turner’s last known intact sketchbook, now in the collection of the Yale Center for British Art. Turner used it on the coast of the English Channel in Kent, in and around Margate, from June to September 1845.The volume is accompanied by a poem in which Tracey Emin (b. 1963) expresses her personal connection with Turner’s work. Emin grew up in Margate, the seaside town that Turner returned to time and again to draw.This presentation of Turner’s sketchbook includes generous margins and blank pages to encourage further sketches, in the spirit of the artist." -- Page 4 of cover
Accompanied by a folded sheet (a poem by Tracey Emin) in the back cover pocket
Keywords: Turner, Joseph Mallord William -- 1775-1851; Turner, J. M. W. / (Joseph Mallord William) / 1775-1851 / Notebooks, sketchbooks, etc; Sketchbooks; Albums de croquis; Bildband